TEACHING THE SPEECH ACT OF REQUEST THROUGH THE COMMUNICATIVE APPROACH (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Speech acts are fundamental components of human interaction, reflecting how speakers use language to perform communicative actions. Among them, requests are central to daily communication and require both linguistic and pragmatic competence. The present paper examines the role of the communicative approach in teaching the speech act of request in English. It discusses theoretical foundations, pragmatic features, cross-cultural perspectives, and practical classroom techniques, concluding with experimental evidence on the effectiveness of communicative methods in developing students’ ability to make contextually appropriate requests.